Analisis Dampak Lingkungan Pembangunan Mall City Garut Plaza (CIPLAZ) - Adi Susetyaningsih; Rega Muhammad Exiana; Muhammad Badru Zaman (Institut Teknologi Garut, 2025)
The development of a modern shopping center such as Mall City Plaza Garut (CIPLAZ) has the potential to cause various impacts on the environment and surrounding communities. This study aims to analyze the environmental impacts caused by this development project using a qualitative descriptive method. Primary data were obtained through field observations and interviews with local residents, while secondary data were collected from official documents such as the Environmental Management Plan (RKL) and Environmental Monitoring Plan (RPL). The results of the study indicate that there are negative impacts on the physical environment, however, the handling of impacts that are in accordance with the RKL and RPL means that these negative impacts do not disturb or harm the affected community.